DIVERSITY AND MARKETING POTENTIAL OF NON-WOOD FOREST PRODUCTS IN BERTEA LOCALITY (PRAHOVA COUNTY) - Cristian Mihai ENESCU; Mihail Cătălin BELCIUG (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Europe, in the last two-three decades, the sector of non-wood forest products (NWFPs) received a special attention, thanks to their multiple uses. The most famous and used NWFPs in Romania which are harvested from the spontaneous flora are represented by the edible mushrooms and truffles, aromatic and medicinal plants, and forest fruits. Across the country, there are districts with high potential in harvesting these forest products, Prahova County being one of them. According to current legislation, the county is divided into two municipalities, twelve towns and ninety communes, including Bertea. The purpose of this research was to assess the potential of harvesting and marketing of the NWFPs in Bertea. A questionnaire with eleven questions was applied in the timeframe between 20th of April and 20th of May 2018 and one hundred households were the subject of the survey. The main way of procuring NWFPs is through harvesting by a family member, only a few people buying these products from local markets. The marketing of the NWFPs in Bertea is almost none, most of the people using the NWFPs for familial purposes and in small quantities. The majority of the interviewed people don’t think that the marketing of the NWFPs should be promoted or collaboration between local stakeholders should be established.